Convergence and community: the Americas in 1993: report (Inter American Dialogue WashingtonUS, 1992)
Focuses on how to create a genuine Western Hemispheric free trade system and eventually a hemispheric economic community. Looks at the collective defense of democracy. Calls attention to the massive poverty and profound inequalities that pervade so many countries of the Americas. Sets forth a common policy agenda and makes concrete recommendations.
DC